STUDENTS SELF-PRESENTATION STRATEGIES ON INSTAGRAM - Imam Handoyo; Tansri Adzlan Syah; Setriani Setriani (Psyche: Jurnal Psikologi, 2026)
This study explores online self-presentation strategies among Indonesian university students who actively use Instagram. Employing a descriptive qualitative design, two participants (SR and MT) were selected based on their high level of engagement on the platform and their willingness to provide access to both primary and secondary Instagram accounts. Data were collected through in-depth interviews, observational analysis of Instagram activities, and content documentation. The data were analyzed using Miles and Hubermans interactive model to identify key patterns of digital self-presentation. The findings reveal five core self-presentation strategies aligned with Hogans (2010) digital dramaturgy framework: performance, exhibition, curation, audience selection, and archive control. SR demonstrated a spontaneous and reflective self-presentation style grounded in authenticity, whereas MT employed deliberate curation to construct a professional and aesthetically refined digital identity. These findings indicate that Instagram functions as a dynamic digital stage in which students strategically manage impressions in accordance with social contexts and identity goals. This study contributes to the growing discourse on digital culture by illustrating how Indonesian university students negotiate authenticity and professionalism in their online self-presentation practices.